2021
DOI: 10.1371/journal.pcbi.1008832
|View full text |Cite
|
Sign up to set email alerts
|

Collective predator evasion: Putting the criticality hypothesis to the test

Abstract: According to the criticality hypothesis, collective biological systems should operate in a special parameter region, close to so-called critical points, where the collective behavior undergoes a qualitative change between different dynamical regimes. Critical systems exhibit unique properties, which may benefit collective information processing such as maximal responsiveness to external stimuli. Besides neuronal and gene-regulatory networks, recent empirical data suggests that also animal collectives may be ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 79 publications
0
43
0
Order By: Relevance
“…We also found that a minimum in cohesion at the transition exists for fixed-speed models, but weakens or even vanishes with increasing speed variability. This has important implications for studies that investigate collective behavior at criticality [19]. For example, a weak cohesion is associated with a high probability of group splits (smaller group size) and lower densities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also found that a minimum in cohesion at the transition exists for fixed-speed models, but weakens or even vanishes with increasing speed variability. This has important implications for studies that investigate collective behavior at criticality [19]. For example, a weak cohesion is associated with a high probability of group splits (smaller group size) and lower densities.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the interaction between fish is modelled by using the continuous version (i.e. overlapping instead of discrete zones) of a well established three-zone model that traditionally uses fixed speed [19]. The force acting on an individual i has a selfpropulsion term (including noise) and a social term.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they found that phase transition is realized even without noise. One popular interesting outcome of these kinds of studies, which helps us to find similar behavior in collective motions of living systems, is the criticality hypothesis in living systems [14][15][16]. According to this hypothesis, collective motions in bio-systems can be observed in the special conditions where the macroscopic dynamics of the systems are improved, and long-range correlation is observed in the group motion to find the optimal living activities [16,17].…”
Section: Introductionmentioning
confidence: 99%